Novel biopreservatives to enhance the safety and quality of strawberry juice - Tomadoni, Bárbara María (2016)
Abstract Pomegranate extract, vanillin and geraniol werestudied as natural antimicrobials on strawberry juice.Strawberry juice was treated with each agent at two concentrations:pomegranate extract at 180 and 360 μg/mL; vanillinat 2.5 and 5 mg/mL; and geraniol at 0.6 and 1.2 μL/mL. Afterbeing treated, juices were stored at 5 °C and microbiological,physicochemical and sensory studies were carried out. Also, asecond batch of juice was inoculated with Escherichia coliO157:H7 (105 CFU/mL) before being treated, to safety study.Geraniol and vanillin, at both concentrations tested, werehighly effective in reducing the native microflora on strawberryjuice (more than 3 log cycles), extending the microbiologicalshelf-life of the product. Moreover, both antimicrobialsimproved the product safety by reducing inoculated E. coliO157:H7. Furthermore, vanillin showed a significant increasein polyphenol content compared to untreated juice. On theother hand, pomegranate extract applied at the highest concentrationshowed important reductions on mesophilic andpsychrophilic bacteria, but no effect on yeast and molds andinoculated E. coli. Even though vanillin and geraniol incorporationon strawberry juice had a negative effect on its sensoryquality, pomegranate extract had no impact on the sensoryattributes evaluated. Combinations of the biopreservativescould be studied in order to decrease the concentration of theantimicrobials, reducing the effects on strawberry juice sensorycharacteristics.